Early steps physical education curriculum theory and practice for children under 8 - Zachopolou, Evridiki; Ian; Tsangaridou, Niki; Liukkonen, Jarmo (Human Kinetics, 2010)
This book offers both theory and practice for those who realise the potential value of movement in young children's lives and wishes to know and do more. This book provides a study of the theory of using movement education as a learning tool for preschool children